The correlation between snot-22 and visual analogue scale in the assessment of symptom severity in chronic rhinosinusitis (2019)
Chronic rhinosinusitis is an inflammatory process involving the sinonasal mucosa, lasting 12 weeks or longer. It is often characterized by a complex of debilitating symptoms usually classified into minor and major symptoms. Estimating symptom/ disease severity using structured questionnaires can be challenging. This is especially so in rural areas where a combination of low literacy levels and language barrier may present communication difficulties. In view of the aforementioned challenges, it has become imperative to explore the correlation between the 22- item sino-nasal outcome test (SNOT-22) and a simpler means of evaluating symptom severity in chronic rhinosinusitis; hence this study. To determine the correlation between SNOT-22 and visual analogue scale (VAS) questionnaire scoring of symptom severity in chronic rhinosinusitis. This was a twelve month prospective cross sectional study of fifty- two consecutive newly diagnosed adult patients with chronic rhinosinusitis. Age of patients ranged from 19 – 91 years. Male to female ratio was 1: 1.26. There was a significant positive correlation between VAS and SNOT-22 in moderate and high symptom severity in patients with CRS. This study found a positive correlation between SNOT-22 and VAS scoring of disease severity in moderate and severe diseases and an insignificant correlation between these two instruments in mild disease. VAS can be used as a guide to symptom severity in the pre-treatment patients with CRS